2012
DOI: 10.1002/jssc.201200333
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy control by breath profile with application of SPMEGC/MS method

Abstract: Chemotherapy used as a treatment against lung cancer has influence on metabolic processes occurring in healthy cells. The changes of biochemical pathways proceeded inside cells might be observed in expired air. In the experiment, breath analysis was carried out before and after anticancer therapy. Expired air samples were collected from 22 patients with a biopsy confirmed lung cancer. Volatile organic compounds present in breath were analyzed by gas chromatography/mass spectrometry. For enrichment of analytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
(16 reference statements)
0
12
0
1
Order By: Relevance
“…Recent efforts in pursuits of a real-time on-line breath analyzer with high data throughput are fruitful [9,11,18,19,20,21,22,23,24,25,26,27,28]. Several relatively new MS-based analytical techniques have been developed and tested for on-line breath analysis, including proton transfer reaction mass spectrometry (PTR-MS) [22,23], vacuum-free ion mobility spectroscopy (IMS) [24,25], and selected ion flow tube mass spectrometry (SIFT-MS) [9,11,26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts in pursuits of a real-time on-line breath analyzer with high data throughput are fruitful [9,11,18,19,20,21,22,23,24,25,26,27,28]. Several relatively new MS-based analytical techniques have been developed and tested for on-line breath analysis, including proton transfer reaction mass spectrometry (PTR-MS) [22,23], vacuum-free ion mobility spectroscopy (IMS) [24,25], and selected ion flow tube mass spectrometry (SIFT-MS) [9,11,26].…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatographymass spectrometry (GC-MS) [5][6][7][8][9][10] has been regarded as a gold-standard method for trace gas analysis for its high sensitivity and high accuracy. However, the GC-MS method is not suitable for breath analysis using a large number of samples due to its complicated sample preparation procedure, time-consuming test process, and high instrumentation and operational costs.…”
Section: Introductionmentioning
confidence: 99%
“…Laser magnetic resonance spectroscopy can be a simple alternative to mass spectrometry in detection of exhaled 14 C-urea in Helicobacter pylori infection [226, 227]. A method of gas chromatography combined with ultraviolet spectroscopy has been used to measure exhaled acetone and isoprene levels in diabetic school children [228] and to monitor pulmonary cancer-cytostatic chemotherapy efficacy [39]. Polymer-coated surface-acoustic-wave resonators are portable instruments which have been introduced and are able to analyze organic vapors [229].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of microsatellite alterations (MAs) of 3p in the EBC deoxyribonucleic acid (DNA) of patients with nonsmall cell pulmonary cancer revealed that MAs in EBC DNA of cancer patients were significantly more common than in normal subjects and MA profile of EBC DNA corresponded to that from cancer tissue of each patient [38]. Isoprene and acetone were shown to increase in the exhaled breath measured by SPME-GC-MS breath test after cytostatic chemotherapy indicating the usefulness of this technique in monitoring of pulmonary cancer-chemotherapy efficacy [39]. Some recent studies revealed reduction of mutated KRAS oncogene in EBC [40] and some VOCs in exhaled breath [41] after surgical resection of pulmonary tumor, particularly nonsmall cell type.…”
Section: Exhaled Markers In Pulmonary Cancermentioning
confidence: 99%